The CEREC system in the making of fixed partial prosthesis in ceramics: A clinical case report (Research, Society and Development, 2021)
Indirect restorations are commonly manufactured in specialized prosthesis laboratories requiring more steps because these laboratories usually rely on a calibrated technician with experience and skill, in addition to receiving various jobs from different dentists. Like response to the dependence of dental surgeons on denture laboratories, the emergence of Computer-Aided Design (CAD / CAM) technology has been transforming the way indirect restorations are performed. CAD / CAM is an evolution of computer science and engineering to the needs of dentistry and has increased dramatically over the last decade thanks to the rapid development of digital computer technology by means of intraoral scanner and milling machine which can be run several systems such as CEREC. Thus, it is possible to optimize the consultations, presenting excellent aesthetic results and clinical longevity. With the CEREC system for dentists, the whole laboratory stage can be developed by the dentist himself inside the dental office. This article aims to present the CEREC system clarifying its intuitive handling through the clinical case report.